Abnormal N400 Semantic Priming Effect May Reflect Psychopathological Processes in Schizophrenia: A Twin Study. (28th August 2017) - Sharma, Anuradha; Sauer, Heinrich; Hill, Holger; Kaufmann, Claudia; Bender, Stephan; Weisbrod, Matthias
Abstract : Objective . Activation of semantic networks is indexed by the N400 effect. We used a twin study design to investigate whether N400 effect abnormalities reflect genetic/trait liability or are related to psychopathological processes in schizophrenia. Methods . We employed robust linear regression to compare N400 and behavioral priming effects across 36 monozygotic twin pairs (6 pairs concordant for schizophrenia/schizoaffective disorder, 11 discordant pairs, and 19 healthy control pairs) performing a lexical decision task. Moreover, we examined the correlation between Brief Psychiatric Rating Scale (BPRS) score and the N400 effect and the influence of medication status on this effect. Results . Regression yielded a significant main effect of group on the N400 effect only in the direct priming condition (p = 0.003 ). Indirect condition and behavioral priming effect showed no significant effect of group. Planned contrasts with the control group as a reference group revealed that affected concordant twins had significantly reduced N400 effect compared to controls, and discordant affected twins had a statistical trend for reduced N400 effect compared to controls. The unaffected twins did not differ significantly from the controls. There was a trend for correlation between reduced N400 effect and higher BPRS scores, and the N400 effect did not differ significantly between medicated and unmedicated patients. Conclusions . Reduced N400 effect may reflect disease-specific processes in schizophrenia implicating frontotemporal brain network in schizophrenia pathology.